Pembelajaran Berbasis Masalah Dengan Strategi Konflik Kognitif Terhadap Penguasaan Konsep Dan Kemampuan Berpikir Kritis Fisika Siswa Kelas XI SMKN 1 Lingsar Tahun Pelajaran 2015/2016 - Nurul Fatimah; Gunawan Gunawan; Wahyudi Wahyudi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
This study aimed to determine the effect of the problem based learning with cognitive conflict strategy towards mastery of concepts and critical thinking skills physics class XIth at SMKN 1 Lingsar academic year 2015/2016. Mastery of concepts measured on the cognitive domain of C1 through C6 (knowledge, comprehension, application, analysis, evaluation and creation) and critical thinking skills measured by indicators of critical thinking. Type of research is a quasi-experimental research design pretest-posttest control group design. Sampling using random cluster sampling. Classroom study is a class XI TIÃÂ  as an experimental class with 36 people and the number of students in class XI TI 2 as the control class with the number of students 36 people. The data will be analyzed using one way MANOVA.. The results showed that the model of problem-based learning with cognitive conflict strategiy affect the mastery of concepts and critical thinking skills physics class X SMKN 1 Lingsar.